Гендерні особливості політичної діяльності на місцевому рівні України - Ілуца, Тетяна; Илуца, Татьяна; Ilutsa, Tetiana (My University, 2016)
У роботі поступово продемонстровано факт того, що гендерна дискримінація в політичній сфері призводить до стагнації в розвитку суспільства та його всезагальної нерівномірної стратифікації за ознакою статі. Оскільки питання включення жінок у політичну діяльність на всіх рівнях управління стоїть досить гостро й українськими соціологами вже проведено низку досліджень на цю тему, то в статті, передусім, проаналізовано та узагальнено вже відомий контент інформації, зібраний як європейськими, так і українськими дослідниками. У роботі також виокремлено основні проблеми, із якими стикаються жінки, які займаються політичною діяльністю; виділено їхні мотиви залучення до політичної активності, а також окреслено способи вирішення питання гендерного дисбалансу в розподілі представництва статей у місцевих органах управління в Україні. In the era of globalization, that is obvious, that the role of women has to change too. Women try to get equal rights with men in all the spheres of social life: political, economic, cultural. It leads to gender discriminations, especially in the political sphere. Under this circumstance, sexism in politics is the main reason of the stagnation in the development of the society and its general uneven stratification by sex. That is why, it is very important to analyze and summarize the existing content of the information, which was collected by European and Ukrainian researchers, who was working on this topic before. Moreover, the aim of the paper is not only to generalize the information on this question, but also to specify the next issues: to find the main problems, faced by women in political activities, to underline their motivation of being involved in political activity, and to find the ways to resolve the issue of gender imbalance in the sphere of local politic activity in Ukraine.
Gender Features of the Political Sphere on the Local Level of Ukraine
Keywords: гендерний дисбаланс; гендерна дискримінація; жінки в політиці; gender gap; гендерні квоти; патріархальні стереотипи; gender imbalance; gender discrimination; women in politics; gender gap; gender quotas; patriarchal stereotypes